1970
DOI: 10.1128/jb.104.2.989-1009.1970
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasmic Organization of Hyphal Tips Among Fungi: Vesicles and Spitzenkörper

Abstract: Hyphal tips of fungi representing OQmycetes, Zygomycetes, Ascomycetes, Basidiomycetes, and Deuteromycetes were examined by light and electron microscopy and compared with respect to their protoplasmic organization. In all fungi studied, there is a zone at the hyphal apex which is rich irn cytoplasmic vesicles but nearly devoid of other cell components. Some vesicle profiles are continuous with the plasma membrane at the apices of these tip-growing cells. The subapical zones of hyphae contain an endomembrane sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
3

Year Published

1976
1976
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(146 citation statements)
references
References 19 publications
6
137
0
3
Order By: Relevance
“…To the best of our knowledge the present work describes for the first time the cytological features of for many fungal hyphae (Grove & Bracker, 1970 ;Sward, 1981) BAS hyphae can be divided into three developmental zones : (i) apical zone ; (ii) subapical zone ; and (iii) mature (vacuolation) zone. (i) Apical zones of BAS extend 4-5 µm back from the hyphal tips.…”
Section: Cytological Featuresmentioning
confidence: 97%
“…To the best of our knowledge the present work describes for the first time the cytological features of for many fungal hyphae (Grove & Bracker, 1970 ;Sward, 1981) BAS hyphae can be divided into three developmental zones : (i) apical zone ; (ii) subapical zone ; and (iii) mature (vacuolation) zone. (i) Apical zones of BAS extend 4-5 µm back from the hyphal tips.…”
Section: Cytological Featuresmentioning
confidence: 97%
“…Despite the supposed ubiquity of clathrin in eukaryotic endocytosis, coated vesicles have rarely been seen in micrographs produced by transmission electron microscopy in hyphae and other filamentous fungal cell types (Bracker, 1967;Grove and Bracker, 1970;Howard, 1981;That et al, 1987;Hoffmann and Mendgen, 1998;Fischer-Parton et al, 2000;Hohmann-Marriott et al, 2006;Bourett et al, 2007), and whether endocytosis in filamentous fungi is primarily clathrin-dependent or Clathrin in A. nidulans 311 independent has remained unresolved. Mechanisms for clathrin-independent endocytosis are well known in mammals and have recently been analyzed in yeast, where they are controlled by proteins generally associated with actin cables, such as formin (Prosser et al, 2011;Mayor et al, 2014).…”
Section: Clathrin Involvement In Endocytosis In a Nidulans And Othermentioning
confidence: 99%
“…One is the Spitzenkörper, a structure located underneath the apical plasma membrane. Ultrastructural studies have shown that the Spitzenkörper largely consists of vesicles (Grove and Bracker, 1970;Howard, 1981;Hohmann-Marriott et al, 2006). Intermingled with these vesicles is a dense mesh of actin microfilaments (Hohmann-Marriott et al, 2006), corresponding to the apical spot seen with GFP-actin and Lifeact-GFP/TagRFP in A. nidulans and Neurospora crassa respectively (Taheri-Talesh et al, 2008;Berepiki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%